Time-varying effects of the gold price and the oil price on imports in Turkey - Kose, Nezir; Unal, Emre; Gayaker, Savas (Routledge Journals, Taylor & Francis Ltd, 2024)
The impacts of the gold price, the oil price and the exchange rate on imports are analyzed using a time-varying parameter vector autoregressive with stochastic volatility (TVP-VAR-SV) model. The impulse response functions showed that the impact of oil price shocks on imports continued for a short period of time, whereas that of the gold price became more significant and gave rise to long term effects in later periods. The results reveal important implications for policy makers reducing imports, which stimulates a trade deficit in Turkey.
Keywords: Gold price; Kalman filters; oil price; TVP-VAR-SV model